Active Community-Based Case Finding for Tuberculosis With Limited Resources: Estimating Prevalence in a Remote Area of Papua New Guinea. (January 2017) - Karki, Bindu; Kittel, Guenter; Bolokon, Ignatius; Duke, Trevor
Papua New Guinea is one of the 14 highest-burden countries for tuberculosis (TB) infection, but few community-based studies exist. We evaluated a low-cost method of active community case finding in Kabwum and Wasu in Morobe Province, Papua New Guinea. Over 3 months we visited 26 villages and screened adults and children for symptoms and signs of TB. Sputum samples were examined using smear microscopy. A total of 1700 people had chronic symptoms, of which 267 were suspicious for TB on further examination. Sputum from 230 symptomatic adults yielded 97 samples that were positive for acid-fast bacilli. In addition, 15 cases of extrapulmonary TB in adults and 17 cases of TB in children were identified. One hundred and thirty people were identified with active TB disease among the source population of approximately 17 000, giving an estimated prevalence of 765 per 100 000. One hundred and six (82%) cases were not previously diagnosed. The cost per case identified was US$146. It is feasible to conduct active community-based case finding and treatment initiation for TB with limited resources and in remote areas, and in Papua New Guinea the yield was high. Active case finding and follow-up of treatment in villages is needed to address the hidden burden of TB in Papua New Guinea and other high-burden Asia Pacific countries.